Construction of two AIE luminogens comprised of a tetra-/tri-phenylethene core and carbazole units for non-doped organic light-emitting diodes. (February 2018) - Shi, Heping; Wang, Shujuan; Qin, Liyuan; Gui, Chen; Zhang, Xinlei; Fang, Li; Chen, Shuming; Tang, Ben Zhong
Abstract: In this work, we report the synthesis of two aggregation-induced emission materials (PPBC andDPPBC ) with different conjugate strengths of penylethene-carbazole moieties. Their structures have been characterized by nuclear magnetic resonance spectroscopy, high-resolution mass spectra and elemental analysis. Besides, their thermal, photophysical, electrochemical and electroluminescent properties are investigated systematically. Their electrical structures are also studied by theoretical methods. The results reveal that they possess good thermal property of decomposition temperature (313 and 214 °C) and low LUMO energy of −1.91 and −1.87 eV.PPBC andDPPBC also show good electrochemical stabilities and optical properties. Non-doped OLED (device I) adopting PPBC as a deep blue emitter presents deep blue emission (the peak is at 441 nm) with CIE coordinates (0.21, 0.22), possessing a turn-on voltage of 4.8 V, a maximum luminance of 7500 cd m −2, a maximum luminance efficiency of 1.286 cd A −1 and a maximum power efficiency of 1.339 lm/w; and non-doped OLED (device II) fabricated by DPPBC emits blue-green light (the peak is at 508 nm) with CIE coordinates (0.23, 0.45), achieving a turn-on voltage of 3.6 V, a maximum luminance of 10290 cd m −2, a maximum luminance efficiency of 4.075 cd A −1 and a maximum power efficiency of 2.559 lm/w. The results demonstrate that these new AIE compounds are promising solid-state luminescent materials with practical utility in non-doped OLED. Graphical abstract: Highlights: Two novel compounds (PPBC andDPPBC) comprised of tri-/tetra-phenylethene skeleton and carbazole units are synthesized. They exhibit aggregation induced emission (AIE) properties. Efficient non-doped devices fabricated withPPBC andDPPBC show good blue or blue-green electroluminescent performance.